Biochar from the mixture of poultry litter and charcoal fines as soil conditioner: Optimization of preparation conditions via response surface methodology. (September 2021) - Ronix, Amanda; Cazetta, André L.; Ximenez, Gabriel R.; Spessato, Lucas; Silva, Marcela C.; Fonseca, Jhessica M.; Yokoyama, Jéssica T.C.; Lopes, Greice K.P.; Zanella, Heloisa G.; Almeida, Vitor C.
Abstract: The use of biochars (BC) in soils is considered an emerging technological. In this work, a BC was prepared from the mixture of poultry litter (PL) and charcoal fines (CF), and its application as soil conditioner was evaluated. Additionally, experimental parameters of BC as carbonization temperature and time, and PL:CF ratio ( wt:wt ) were optimized via chemometrics tools, aiming to obtain an optimized biochar (BCop ) with high values of BET surface area ( S BET ), cation exchange capacity (CEC) and yield. The optimum condition found for preparation of BCop was: carbonization temperature of 450 °C, time of 300 min and PL:CF ratio of 1.4 ( wt:wt ), which provided a BCop with S BET of 99 m 2  g −1 ; CEC of 2.21 cmolc  Kg −1 and yield of 54.73%. The application of the BCop as potential soil conditioner promoted changes in features of soil and the dosage of 5% showed the best response for the cabbage cultivation. Graphical abstract: Unlabelled Image Highlights: Biochar was naturally enriched with macro and micronutrients. Optimized biochar (BCop ) exhibited higher CEC, surface area and yield. 5% of BCop dosage promoted an improvement in cabbage growth. BCop promoted an increase of macro and micronutrients in the soil.